Totuma, Somos Maíz (2021)
The objective of this project of entrepreneurship, is to create a conceptual and experiential restaurant in the Municipality of Mosquera, whose heart is the design; that is, to allow a sensory and emotional experience to the users, by means of different ramifications of industrial design, grouped and applied in a place where the main activity (but not the only one), is the consumption of food around a Muisca cultural concept. The main intention is to create a new path for us as designers, instead of leaving school to get a traditional job, it is better to go out to generate it and contribute to the economic, social and cultural development of the municipality, and the evolution of the concept of industrial design in the country.